Effects of Bitter Melon (Momordica charantia L.) and Starfruit (Averrhoa bilimbi L.) on Proinflammatory Cytokines Produced by Hyperglycemic Mice Model - Wardani, Bella Pradina Novinda; Rahayu, Sri; Rifa'i, Muhaimin (The Journal of Experimental Life Science, 2020)
Hyperglycemia is a condition of excessive blood glucose in blood plasma caused by damage to the pancreatic beta-cell structure that causes impaired insulin secretion. This study aimed to investigate the combination of Bitter Melon and Star Fruit ethanol extract (SBME) on pro-inflammatory cytokines production in hyperglycemic albino mice models. This study was treated in 25 female albino mice weighing 25-30 and 9 weeks old. STZ was given in a dose of 145 mg.kg-1 BW intraperitoneally. Hyperglycemic mice were given orally with SBME ethanol extract at doses 10, 40, and 160 mg.kg-1 BW for two weeks. After treatment, pro-inflammatory molecules were analyzed by flow cytometry from the splenic cell. This study showed that SBME treatment can reduce the production of pro-inflammatory cytokines especially IL-1b, but increases IL-6 in hyperglycemic mice. After treatment with SBME at a dose of 40, the IL-1b pro-inflammation molecule decreased significantly (p>0,05). It reached a normal physiological level, but the dose has not been able to reduce the IL-6 pro-inflammation molecule significantly. The conclusion of this study was Bitter Melon and Star Fruit ethanol extract (SBME) with a treatment of 40 mg.kg-1 BW can suppress IL-1b pro-inflammatory cytokines in hyperglycemic mice models, but has not been able to reduce the expression of IL-6 pro-inflammatory cytokines. Suggesting this medicinal herb might be a useful strategy for future therapeutic interventions in degenerative diseases or diseases involving cell activation, but a study of doses is needed.Keywords: Averrhoa bilimbi L., Hyperglycemia, Inflammation, Momordica charantia L.